IMPROVING STUDENTS’ ABILITY IN WRITING PERSONAL EXPERIENCE THROUGH CLUSTERING TECHNIQUE AT THE SEVENTH GRADE STUDENTS OF SMPN 01 BETUNG BANYUASIN - Edi Suryadi; F.A. Milawasri (Jurnal Didascein Bahasa, 2017)
The objective of study was to improve the students‘ ability in writing personal experiences through clustering techniques to the seventh grade students of SMPN 01 Betung. The research method was the classroom action research (PTK) that consist of three cycles. Each cycles consists of four stages that are planning, acting, observing and reflecting. The cycle 1 was conducted on February 3, 2017, The cycle II was on February 17, 2017 and cycle III was on February 22, 2017. The subject of this study were 34 students. The techniques for collecting the data used were observation of students activities and the results of writing test from each cycle. The indicator of succesful implementing this strategy was that the students had achieved the writing score which is higher than minimum criteria mastery learning score (KKM >65). The results of observation showed that the average score from each cycle was 70.6%. The average score of cycle 1 was 61.79 with standard studying mastery was 44,12%. The average score of cycle 2 was 66.15 with standard studying mastery was 67.65%. The average score of cycle 3 was 76.03 with standard studying mastery was 85.29%. Based on the results of study, it can be concluded that the students‘ ability writing personal experience through clustering techniques improved significantly.Keywords: ability, writing personal experience, clustering technique.